Pengaruh Profitabilitas, Kepemilikan Institusional, Kebijakan Dividen dan Leverage Terhadap Nilai - Nuri Ari Hidayat; Umaimah Umaimah (JIATAX (Journal of Islamic Accounting and Tax), 2020)
This study aims to determine how much influence profitability, institutional ownership, dividend policy, and leverage on firm value at LQ 45 companies in 2016-2019. This research uses quantitative methods and uses secondary data as a data source. The sampling technique used was the purposive sampling technique and obtained data of 108 company samples. The data analysis technique used is multiple linear regression analysis. The results showed that profitability, which is proxied by return on equity (ROE), affects firm value. Institutional ownership variable which is proxied by institutional (INST) and dividend policy which is proxied by dividend payout ratio (DPR) does not affect firm value. The leverage variable which is proxied by the debt to asset ratio (DAR) affects firm value in a negative direction.